IMPLEMENTASI MANAJEMEN KELAS DALAM PEMBELAJARAN AKIDAH AKHLAK PADA SISWA KELAS V DI MADRASAH IBTIDAIYAH IKHLAASHUL ‘AMAL SEBAWI - Syawitri Syawitri (Tarbiya Islamica, 2015)
The purpose of this study is to reveal about: 1) Class management planning in learning akidah akhlak for grade V students at Madrasah Ibtidaiyah Ikhlaashul 'Amal Sebawi, Sebawi District, Academic Year 2019-2020. 2) Implementation of class management in learning akidah akhlak for fifth grade students at Madrasah Ibtidaiyah Ikhlaashul 'Amal Sebawi, Sebawi District, Academic Year 2019-2020. 3) Evaluation of class management in learning akidah akhlak for fifth grade students at Madrasah Ibtidaiyah Ikhlaashul'Amal Sebawi, Sebawi District, 2019-2020 Academic Year. This research uses a qualitative approach and descriptive type. Data collection techniques using interviews, observation and documentation. The analysis technique used is data collection, data reduction, data display, verification. The results showed that: 1) Planning for class teachers in learning akidah akhlak for grade V students at Madrasah Ibtidaiyah Ikhlaashul 'Amal Sebawi Sebawi District Academic Year 2019-2020: a) formulating learning objectives b) preparing material c) formulating methods d) preparing media. 2) Implementation of class management in learning akidah akhlak for grade V students at Madrasah Ibtidaiyah Ikhlaashul'Amal Sebawi, Sebawi District, 2019-2020 Academic Year: a) providing exemplary b) doing habitualization or habituation c) creating a conducive atmosphere d) giving direct warning e ) motivation. 3) Evaluation of class management in learning akidah akhlak for fifth grade students at Madrasah Ibtidaiyah Ikhlaashul'Amal Sebawi, Sebawi District, 2019-2020 Academic Year. a) viewed from the individual student behavior b) in terms of the teaching program.